`Truly Be Me' Supporting Children in the Community who have Experienced Domestic Violence and Abuse - Hollywood, Eleanor; O'Neill, Tracey (Trinity College Dublin, 2025)
An evaluation of the Child and Youth Programme Community which forms part of the Child and Youth Service at Meath Women’s Refuge and Support Services (MWRSS) was conducted to review the practice and impact of the programme since its inception in 2018. The overall aim of the research was to evaluate the programme as it operates currently and to look to support the growth and development of the programme into the future. The evaluation was accomplished using case study research which involved conducting in-depth interviews with children, mothers and stakeholders associated with the planning, organisation and delivery of the Child and Youth Programme Community at MWRSS.
PUBLISHED
Keywords: Domestic Violence, Domestic Abuse, Children, Recovery; Inclusive Society; Other; Children; Home and community living; Justice and safeguarding; Legislation; Relationships; Social participation; Social services, interventions and supports